Practical implementation of International Financial Reporting Standards : lessons learned (UN New YorkUS, 2008)
Provides details of major practical implementation challenges and lessons learned from the experiences of member states that have embarked on the implementation process of IFRS. Presents country case studies of Brazil, Germany, India, Jamaica, Kenya, Pakistan, South Africa and Turkey.
Keywords: ACCOUNTING